Biogeochemistry measurements from profiles collected during cruise GLICE in Disko Bay, RV Sanna, August 2022 - Hopwood, Mark James; Carroll, Dustin; Cozzi, Stefano; Cantoni, Carolina; Körtzinger, Arne (PANGAEA, 2025)
Vertical profiles were collected around Disko Bay in August 2024 focusing mainly on the upper 100 m of the water column which is affected by meltwater from Greenland. Samples were retained for macronutrients (nitrate, phosphate and dSi), DOC/DON, and carbonate chemistry (total alkalinity and pH). Bottle files from the CTD casts (SBE 911plus, Sea-Bird) are included with the measurements. Further details are available from the cruise report.
Keywords: Carbonate chemistry; Disko Bay; Glacier; Greenland; Meltwater; nutrients